An Analysis of Primary Hyperparathyroidism in Individuals Diagnosed with Multiple Endocrine Neoplasia Type 2 - Ana-Maria Gheorghe; Claudiu Nistor; Alexandru-Florin Florescu; Mara Carsote (Diseases)
Background: Primary hyperparathyroidism (PHPT) represents a multi-faced disease with a wide spectrum of manifestations. Familial forms of PHPT (affecting up to 10% of the cases) involve a particular category that encompasses a large range of hereditary syndromes, including parathyroid hyper-function, frequently in the setting of a multi-glandular disease. Objective: The aim was to analyze the most recent findings regarding PHPT in multiple endocrine neoplasia type 2 (MEN2) to a better understanding of the timing with respect to the associated ailments, MEN2-related PHPT (MEN2-PHPT) clinical and genetic particularities, optimum diagnostic, and overall management, particularly, surgical outcomes. Methods: This was a PubMed-based compressive review with regard to the latest data published in English from January 2020 until January 2025, using the following keywords: “primary hyperparathyroidism” and “multiple endocrine neoplasia”, “multiple endocrine neoplasia type 2”, “MEN2”, or “MEN2A”. We included original full-length studies of any study design that provided clinically relevant data in MEN2-PHPT and excluded reviews, meta-analysis, and case reports/series. Results: A total of 3783 individuals confirmed with MEN2 or RET pathogenic variants carriers were analyzed across 14 studies that provided data on PHPT. The prevalence of MEN2-PHPT subjects varied between 7.84% and 31.3%, with particularly low rates in non-index patients (3.8%). PHPT was the first syndrome manifestation in 0.9% of MEN2 patients. In terms of gender distribution, females represented 42.85% or 54.9% (similar rates between women and men, and only a single cohort showed a female rate up to 80%). Most subjects were diagnosed with PHPT and underwent surgery in the third or fourth decade of life. The highest median age at MEN2 diagnosis was 42 years. The youngest patients were RET pathogenic variants carriers who underwent (genetic) screening with median ages of 12 or 14 years. RET pathogenic variants analysis (n = 10/14 studies) showed that 16.67% of patients with p.Cys634Arg and 37.5% of those with p.Cys611Tyr had symptomatic PHPT, while those with p.Cys618Phe and p.Leu790Phe were asymptomatic. Timing analysis with respect to the medullary thyroid carcinoma diagnosis showed synchronous PHPT diagnosis in 80% and metachronous in 10% of MEN2 patients; with respect to MEN2-pheochromocytoma, synchronous diagnosis of PHPT was found in 56%, while pheochromocytoma was identified before PHPT in 22% of the cases and after PHPT in 22%. Studies (n = 10/14, N = 156 subjects with MEN2-PHPT) on parathyroidectomy identified that 72.7% to 100% of the individuals underwent surgery, typically performed in adulthood, at ages spanning from a mean of 34.7 to 48.5 years. The post-surgery outcomes varied (e.g., the rate for persistent PHPT was of 0%, 8% to 16.7%; recurrent PHPT of 12.5% to 23%; permanent hypoparathyroidism of 33% to 46%; permanent unilateral vocal cord palsy of 0% up to16.7%). Data regarding the number of involved glands (n = 7, N = 77): the prevalence of multi-glandular disease was pinpointed between 12.5% and 50%. Conclusions: MEN2-PHPT involved unexpected high rates of single-gland involvement (from 33.3% to 87.5%), probably due to an early detection across genetic screening. Traditional female higher prevalence in PHPT was not confirmed in most MEN2 cohorts. As expected, a younger age at PHPT diagnosis and surgery than seen in non-MEN2 patients was identified, being tidily connected with the syndromic constellation of tumors/malignancies. Overall, approximately, one out of ten patients were further confirmed with MEN2 starting with PHPT as the first clinically manifested element.